Aromaterapi Lemon terhadap Intensitas Mual Muntah Pasien Kanker Pasca Kemoterapi - Sijabat, Elinda Juniwati; Tanjung, Dudut; Salim, Emil (Journal of Telenursing (JOTING), 2024)
Study This for identify effectiveness lemon aromatherapy against nauseous vomit on receiving patients​ chemotherapy in room take care stay chemotherapy House Sick Pure Teguh Medan. Method research used​ on study This is a quasi experiment with a total of 72 respondents consisting of of 36 people group control and 36 people group selected intervention​ with technique consecutive sampling. Results analysis statistics with use test Mann-Whitney Test shows results There is difference nauseous vomit between group control And group intervention after giving lemon aromatherapy (p=0.000). Conclusion is known lemon aromatherapy can For lower intensity nauseous vomit patient undergoing cancer​ chemotherapy And recommended as Wrong One intervention nursing independent For lower nauseous vomit on patient cancer . Keywords: Aromatherpy, Lemon, Nausea and Vomiting, Cancer, Chemotherapy